Seca, deslocamentos e serviços de emergência: a experiência dos trabalhadores da construção do açude araras (1951-1958). - Rodrigues, Francisco Magnel Carvalho (2020)
At this moment, the dissertation intends to discuss the migratory processes and the experiences of workers in the construction services of Araras sugar, located in the municipality of Varjota, located in the North Zone of Ceará, in the middle course of the Rio Acaraú, 270 miles from Fortaleza, capital of State . A dam, created under the tutelage of the National Department of Works Against Segas (DNOCS), was inaugurated on July 31, 1958. Transformed into emergency services for retirees during the droughts of 1951-1953 and 1958, a time frame of our research, attracted thousands of people looking for a job. When confronting sources of different natures, we look for problematic answers, such as: who were the subjects in question? What motivations did you consider to choose the works of Açude Araras as a local destination? How do we perceive this experience, reconstitute it as spatial dynamics and their identities? How to resist the impositions in the social conflict experienced? The maintenance of these operators is not allowed, as the principle would be provisional, exercising the possibility of transfers, fixation and rotation of residents. Later, as related to oral sources, this camp was transferred to another area in the late 1960s, developing and integrating a city, Varjota. This mode, such migrations is shown as a multifaceted phenomenon, extrapolating an economic sphere, since it points to socio-cultural interactions. In the studied process, how common experiences in the daily lives of these migrants reveal the construction of an awareness of antagonisms, collaboration, rights and resistance and explorations and precariousness of their living conditions in an intended proletarianization process. Thus, we found that the works of state of emergency, without a period considered, are placed by the official discourse of infrastructure implementation, the modernization of the field and social assistance to retirees in times of drought, but they can also be seen as repertoires and learning from peasants to reproduce their ways of life.